INCREASING LECTURER PERFORMANCE THROUGH ORGANIZATIONAL CLIMATE, INTERPERSONAL COMMUNICATION, TRANSFORMATIONAL LEADERSHIP WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Khaeruman, Khaeruman; Hubeis, Musa; Yusnita, Nancy (Yayasan Education and Social Center, 2023)
This research aims to determine efforts to improve performance through organizational climate, interpersonal communication, and transformational leadership and job satisfaction as intervaning variables. This research uses a survey method by collecting data through questionnaires distributed to 285 lecturers at 6 private universities in the city of Serang, Banten. This research uses a combined research method (mixed methods). Researchers use this type of design which is analyzed using path analysis. The results of this research show that Organizational Climate, Interpersonal Communication, and Transformational Leadership have a significant positive direct influence on the Job Satisfaction of lecturers at the Private University of Serang Banten City. Strengthening these aspects can increase Job Satisfaction. Apart from that, there is a direct positive influence of Organizational Climate, Interpersonal Communication, and Job Satisfaction on lecturer performance. Strengthening the Organizational Climate and Interpersonal Communication can directly improve lecturer performance, while Job Satisfaction also has a direct positive influence on lecturer performance. In addition, the findings show that there is a positive indirect influence of Organizational Climate on lecturer performance through increasing Job Satisfaction. The results of this research provide an important contribution to the development of university management strategies to improve the quality of teaching and lecturer performance in the educational environment. The practical implication of this research is that private university management in Serang City needs to pay attention to and improve organizational climate, interpersonal communication, and transformational leadership as an effort to increase lecturers' job satisfaction, which in turn will have a positive impact on their performance. This research suggestion involves recommendations for improving the performance of private university lecturers in Serang City, Banten. It is recommended that university management focus on developing organizational climate, strengthening interpersonal communication, and engaging in transformational leadership training